Improving Elementary School Student' Mathematical Communication and Self-Efficacy Through Realistic Mathematics Learning Assisted by Canva Media - Novianti, Novianti; Wayudi, Mauliana (Universitas Negeri Makassar, 2024)
The rapid development of technology provides new innovations in the world of education, especially in the process of thinking, communicating, and learning. Mathematical communication ability is one of the important skills to be developed in the 21st century. The purpose of this study was to analyze the improvement of students' mathematical communication skills and self-efficacy with a realistic mathematics learning model assisted by Canva. The research method used was a quasi-experimental study. The research design chosen was a nonequivalent pretest-posttest control group design. The population in the study were all fifth-grade students of UPTD SD Negeri 4 Peusangan, while the sample of this study was 20 fifth- grade students as the experimental class and 18 fifth-grade students as the control class. The instruments used to obtain research data were test and non-test instruments. The test instrument consisted of 4 essay questions while the non-test instrument was a self-efficacy attitude scale test. The results of the study showed that: 1) the increase in mathematical communication skills of students who received realistic mathematics learning assisted by Canva media was higher than those who received conventional learning, 2) the achievement of self-efficacy of students who received realistic mathematics learning assisted by Canva media was better than those who received conventional learning.